The Trucking Industry in Ontario - McKechnie, Graeme (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
In this case study of the Ontario trucking industry, the author considers the«  for hire » section of the industry and, within this section, emphasizes general freight transport in order to illustrate the advantages and shortcomings of the multi-employer bargaining system.